2005
DOI: 10.1124/jpet.105.093773
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Dimorphic Regulation of Hepatic Isoforms of Human Cytochrome P450 by Growth Hormone

Abstract: Sex differences in drug metabolism have been reported in numerous species, including humans. In rats and mice, sexdependent differences in circulating growth hormone profiles are responsible for the differential expression of multiple sexdependent isoforms of cytochrome P450, which is the basis for the sexual dimorphism in drug metabolism. In contrast, very little is known about sex differences in human isoforms of cytochrome P450 and their regulation by growth hormone. In this study, we have examined the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
76
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 38 publications
5
76
1
Order By: Relevance
“…Since HYPOX depletes the body of at least a dozen hormones, including, not just GH, but those of the thyroid, adrenal and gonads, it isn't possible without far more experiments, to determine which hormones may induce or suppress CYP2C11 in the immune system of both male and female rats. In this regard, thyroid hormone is required for full expression of several hepatic P450s [45], androgens are the primary regulators of kidney CYP2C11 in rats [46] and hepatic P450-dependent enzymes in chickens [47] and glucocorticoids are essential for expression of human CYP3A4 [48].…”
Section: Discussionmentioning
confidence: 99%
“…Since HYPOX depletes the body of at least a dozen hormones, including, not just GH, but those of the thyroid, adrenal and gonads, it isn't possible without far more experiments, to determine which hormones may induce or suppress CYP2C11 in the immune system of both male and female rats. In this regard, thyroid hormone is required for full expression of several hepatic P450s [45], androgens are the primary regulators of kidney CYP2C11 in rats [46] and hepatic P450-dependent enzymes in chickens [47] and glucocorticoids are essential for expression of human CYP3A4 [48].…”
Section: Discussionmentioning
confidence: 99%
“…Previously it has been reported that CYP2E1, 3A4, 1A2, 2A6, and 2B6 are subject to gender influence in humans, but conflicting results have been obtained (Dhir et al 2006;Anderson 2008;Scandlyn et al 2008). Our results support that the activity of CYP3A4 (but not the others reported) is affected by gender, with females having higher activity measurement than males.…”
Section: Discussionmentioning
confidence: 99%
“…These sex differences in the circulating GH profiles and not sexual differences in GH concentrations per se are responsible for observed sexual dimorphisms ranging from body growth to the expression of hepatic enzymes (Jansson et al, 1985;Legraverend et al, 1992;Shapiro et al, 1995). In this regard, rat, murine, and human liver all contain sexdependent isoforms of P450 that are regulated by the sex-dependent profiles of circulating GH (Legraverend et al, 1992;Shapiro et al, 1995;Dhir et al, 2006). Sex-dependent, hepatic P450s in the rat are generally divided into three groups: male-specific isoforms only found in male liver, femalespecific isoforms only expressed in female liver, and sex (generally female)-predominant P450s found in both sexes, but at higher levels in one sex.…”
mentioning
confidence: 99%